Acoustical and Perceptual Analysis of Noise Reduction Strategies in Individuals With Auditory Neuropathy Spectrum Disorders - Jaisinghani, Priyanka; Manjula, P. (Journal of speech, language, and hearing research, 2020)
Purpose: The conventional amplification devices render minimal or no benefit at abating the speech perception problems of individuals with auditory neuropathy spectrum disorder (ANSD). This study was undertaken to evaluate the effect of noise reduction strategies (multiband spectral subtraction, Wiener-as, Karhunen-Loeve transform [Subspace], and ideal binary mask [IdBM] algorithm) on speech using speech perception measures and acoustic measure among individuals with ANSD. Method: Two groups of participants (age: 17-43 years) were recruited in the study. Group I comprised 12 individuals with a confirmed diagnosis of ANSD and not exceeding moderate degree of hearing loss and Group II of 10 individuals with normal hearing in both ears. The signal-to-noise required for 50% speech recognition (SNR-50) was measured for the participants in five conditions, that is, unprocessed speech and speech processed with four noise reduction strategies. Additionally, an acoustic objective measure Extended Short-Time Objective Intelligibility algorithm was employed to estimate the intelligibility index across the conditions. Results: Significant difference was found across conditions in both the groups. Pairwise comparison revealed significantly better speech perception on SNR-50 measure with IdBM strategy, for both the groups. No significant difference in SNR-50 was observed with other noise reduction strategies. IdBM condition also gave the highest intelligibility index (d) values using Extended Short-Time Objective Intelligibility algorithm. This finding needs to be verified on a larger group of individuals with ANSD. Conclusions: IdBM noise reduction strategy rendered significantly lower SNR-50 compared to other noise reduction strategies for individuals with ANSD in this study. This provides clinical evidence for the same and also recommends trying on a larger group of participants before its implementation in hearing devices. Apart from this, the current strategies used in hearing aids provide no improvement in speech identification in noise for this population. Hence, though the present hearing aids may show benefit in quiet condition, chances of its rejection are high in noisy backgrounds.